Optimasi Kolom dan Balok Melalui Value Engineering pada Gedung Asrama SMP IT Al-Ihsan Pasuruan - Sugiarto, Muhammad; Sasongko, Januar (Universitas Batanghari Jambi, 2026)
Infrastructure development in Indonesia requires efficiency in construction planning, particularly for multi-story buildings where structural works account for the largest portion of costs. The superstructure, such as columns and beams, plays a crucial role in supporting loads and ensuring building stability, making design efficiency highly influential on both safety and budget. Problems such as overdesign can lead to material waste and increased project expenses. This study aims to apply Value Engineering (VE) to the superstructure of the SMP IT Al-Ihsan dormitory project in Pasuruan City, focusing on columns and beams to obtain alternative designs that are more economical without reducing structural performance. The research employed a quantitative approach with structural modeling and analysis using ETABS software. Data were obtained from construction drawings, material specifications, and technical documents. The analysis compared the existing design with proposed alternatives, evaluated against axial strength, flexural capacity, and internal force distribution parameters in accordance with SNI 2847:2019 and SNI 1726:2019 standards. The results show that reducing the column dimensions from 50×50 cm to 30×30 cm and beams from 30×60 cm to 25×50 cm still satisfies technical requirements. Material efficiency was achieved by reducing concrete volume by 64% in columns and 30.56% in beams, while maintaining adequate strength and stability. The study concludes that the application of VE to the superstructure can reduce material volume, lower construction costs, and decrease dead loads, which also contributes to reducing seismic loads. The proposed alternative designs are technically feasible, structurally safe, and more economical, making them suitable as a reference for future multi-story building projects requiring cost optimization.